A solar cell and a method of manufacturing the same, a stacked cell, and a photovoltaic module

CN122952726APending Publication Date: 2026-10-20SHANGRAO JINKO SOLAR NO 3 INTELLIGENT MANUFACTURING CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611123195.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

通过一种简单且稳定的制备方法制备MXene@Ag复合材料,将MXene@Ag复合材料与不同形貌银粉和有机载体共混制备具有高导电、优异印刷性能以及低成本的光伏银浆。利用MXene的优异性能以及银纳米颗粒的低温烧结,可以降低导电填料之间的界面电阻,提升低温银浆的导电性能,并且还可以降低银粉的含量,降低制备成本以及具有良好的印刷性能以及粘附性能。同时,MXene复合材料的制备时不采用氟化物,安全性更高,还能避免纳米银产生团聚现象,从而提高导电银浆的导电性能和稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This application relates to a solar cell and its manufacturing method, a tandem cell, and a photovoltaic module. The manufacturing method of the solar cell includes: obtaining a solar cell body and a conductive material; depositing the conductive material on the surface of the solar cell body, and curing it to form at least one of a main grid and a fine grid; the conductive material contains an MXene@Ag composite material, which includes MXene material and Ag nanoparticles; the preparation method of the MXene material includes: grinding and mixing Ti3AlC2 powder with a metal chloride, and then heating and reacting it in an oxygen-free atmosphere to obtain the MXene material. This application uses a fluorine-free method to prepare MXene, which is safer and avoids the relatively poor conductivity, poor dispersibility, and easy agglomeration of fluorine-containing materials, which are detrimental to dispersion in slurries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of photovoltaic technology, and in particular to a solar cell and its manufacturing method, a tandem cell, and a photovoltaic module. Background Technology

[0002] Heterojunction solar cells (HJT solar cells) are a type of novel high-efficiency solar cell, characterized by simple fabrication process, no high-temperature sintering, high conversion efficiency, low temperature coefficient, and no light-induced degradation. The processing temperature of silicon-based HJT solar cells is approximately 200℃, significantly different from the 900℃ processing temperature of traditional crystalline silicon solar cells. Therefore, the high-temperature silver paste used in traditional crystalline silicon solar cells is unsuitable for HJT solar cells; a low-temperature silver paste with a curing temperature below 200℃ must be used. Summary of the Invention

[0003] This application provides a solar cell and its manufacturing method, a tandem cell, and a photovoltaic module, which can at least solve the problem of MXene material dispersion in slurry.

[0004] In a first aspect, this application provides a method for manufacturing a solar cell, comprising: Obtain the solar cell body and conductive materials; The conductive material is disposed on the surface of the solar cell body and cured to form a main grid and / or a fine grid. The conductive material contains an MXene@Ag composite material, which comprises MXene material and Ag nanoparticles. The method for preparing the MXene material includes: Ti3AlC2 powder was ground and mixed with metal chloride, and then heated in an oxygen-free atmosphere to obtain the MXene material.

[0005] Optionally, the temperature of the heating reaction is 550℃~800℃.

[0006] Optionally, the mass ratio of the Ti3AlC2 powder to the metal chloride is 3:1 to 8:1.

[0007] Optionally, the metal chloride includes at least one of copper chloride, zinc chloride, and nickel chloride. The reasons for choosing these metal chlorides are as follows: 1. They have the best oxidation potential compatibility; 2. They have a suitable melting window; and 3. Post-processing for impurity removal is simple.

[0008] Optionally, the particle size of the MXene material is 0.6μm to 6μm; the D50 of the Ag nanoparticles does not exceed 100nm.

[0009] Optionally, the MXene@Ag composite material has a mass fraction of 1% to 10% in the conductive material.

[0010] Optionally, the conductive material further includes silver powder, an organic carrier, a coupling agent, and a curing agent, wherein the mass fractions of the silver powder, the organic carrier, the coupling agent, and the curing agent in the conductive material are 80%~90%, 10%~18%, 0.1%~0.6%, and 0.1%~0.6%, respectively.

[0011] Optionally, the silver powder includes flake silver powder and spherical silver powder, wherein the mass ratio of the flake silver powder to the spherical silver powder is 2:1 to 3:1.

[0012] Optionally, the particle size of the flake silver powder is 2μm to 6μm, and the particle size of the spherical silver powder is 0.3μm to 0.7μm.

[0013] Optionally, the organic carrier includes a binder, an organic solvent, and a thixotropic agent.

[0014] Optionally, the adhesive includes at least one of bisphenol A type epoxy resin and bisphenol S type epoxy resin; the organic solvent includes at least one of diethylene glycol butyl ether acetate, ethyl carbitol acetate, and propylene glycol methyl ether acetate; and the thixotropic agent includes at least one of hydrogenated castor oil and polyethylene wax.

[0015] Optionally, the coupling agent includes a silane coupling agent, and the curing agent includes at least one of boron trifluoride-monoethylamine complex, 2-methylimidazole, and methylhexahydrophthalic anhydride.

[0016] Optionally, the silane coupling agent includes at least one of epoxy silanes and amino silanes, such as γ-aminopropyltriethoxysilane (KH550).

[0017] Secondly, this application provides a solar cell obtained by the manufacturing method of the solar cell described above.

[0018] Thirdly, this application provides a stacked battery, comprising: Crystalline silicon bottom cell, wherein the crystalline silicon bottom cell is a solar cell obtained by the above-described method for manufacturing solar cells, or the above-described solar cell; A perovskite solar cell, wherein the perovskite solar cell is located on one side of the crystalline silicon substrate solar cell.

[0019] Fourthly, this application provides a photovoltaic module, including a battery string, the battery string including a plurality of solar cells obtained by the manufacturing method of the solar cells as described above, or solar cells as described above, or tandem cells as described above, arranged along a first direction, and the plurality of battery strings are further arranged along a second direction; A solder strip extending along a first direction and arranged along a second direction, the solder strip being used to connect two adjacent solar cells or two stacked cells along the first direction; A backplate, located on the side of the solder strip away from the back of the battery string.

[0020] The technical solution provided in this application has at least the following advantages: MXene@Ag composite materials were prepared using a simple and stable method. These composite materials were then blended with silver powders of different morphologies and organic carriers to prepare photovoltaic silver pastes exhibiting high conductivity, excellent printability, and low cost. Utilizing the superior properties of MXene and the low-temperature sintering of silver nanoparticles, the interfacial resistance between conductive fillers can be reduced, improving the conductivity of the low-temperature silver paste. Furthermore, the silver powder content can be reduced, lowering the preparation cost while maintaining good printability and adhesion. Simultaneously, the preparation of the MXene composite material does not involve fluorides, resulting in higher safety and preventing the agglomeration of silver nanoparticles, thereby enhancing the conductivity and stability of the conductive silver paste. Attached Figure Description

[0021] One or more embodiments are illustrated by way of example with corresponding pictures in the accompanying drawings. These illustrations do not constitute a limitation on the embodiments. Unless otherwise stated, the pictures in the accompanying drawings do not constitute a limitation on scale. In order to more clearly illustrate the technical solutions in the embodiments of this application or in the conventional technology, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a schematic diagram of the structure of the solar cell in this application; Figure 2 This is a top view of the photovoltaic module in this application.

[0023] In the diagram: 1. Solar cell body; 2. Main grid; 3. Fine grid; 4. Solder ribbon; 100. Cell string; 101. Solar cell; 111. Solder ribbon; 120. Backsheet. Detailed Implementation

[0024] In the description of the embodiments of this application, the technical terms "first", "second", etc. are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0025] As the background technology shows, ordinary low-temperature silver paste has a solid content of 50% to 80%, mainly using micron-sized flake silver powder as the conductive phase. Due to the low curing temperature, the silver powder cannot directly sinter together and must rely on resin for bonding. Since the resin is non-conductive, low-temperature silver paste generally has a high resistivity (greater than 10 ohms). -5 (Ω·cm). Reducing the resistivity of low-temperature silver paste requires minimizing resin usage. However, increasing the silver content increases the viscosity of the paste, rapidly decreasing its fluidity and increasing preparation costs, hindering its widespread adoption in actual production. Therefore, low-temperature silver paste must possess excellent conductivity, good fluidity, thixotropy, and adhesion at a relatively low silver content. Existing research indicates that achieving a resistivity less than 5 × 10⁻⁶ Ω·cm requires… -6 For low-temperature silver paste with a solid content of Ω·cm, the silver powder content must be greater than 90%. However, high solids content in silver paste increases viscosity, which is detrimental to printing and also increases preparation costs. If the conductive phase in low-temperature silver paste is entirely composed of flake-shaped silver powder, the accumulation of these flakes will lead to poor flowability. Therefore, spherical silver powder needs to be added to fill the pores and improve flowability.

[0026] The main connection method of silver powder in low-temperature silver paste is overlapping, which forms a conductive network to conduct electricity. However, due to the presence of resin between the silver powders, it is difficult to reduce the resistivity to 5×10⁻⁶ using only this conductive method. -5 For temperatures below Ω·cm, it is necessary to introduce nano-silver powder that can be sintered below the curing temperature of silver paste to achieve direct connection between silver powders, thereby reducing the interfacial resistance between silver powders and improving the conductivity of low-temperature silver paste. However, to achieve low-temperature sintering of nano-silver powder, the size of the nano-silver powder must not exceed 100nm. However, nano-silver powder of this size is expensive and prone to agglomeration, which is not conducive to its application in actual production.

[0027] To address this technical challenge, some studies have employed chemical reduction to modify the surface of flake-shaped silver powder with nano-silver, resulting in nano-silver-modified flake-shaped silver powder. This nano-silver powder serves as the conductive phase in low-temperature conductive silver paste. During the curing stage, as the temperature increases, the nano-silver on the surface of the flake-shaped silver powder sinters. The sintered nano-silver connects with adjacent flake-shaped silver powder, forming more conductive pathways in three-dimensional space, thus improving the conductivity of the cured silver paste. However, modifying flake-shaped silver with nano-silver involves a complex preparation process and high costs. Other studies have used micron-sized flake-shaped silver powder as the main conductive phase of the silver paste, mixed with submicron-sized and nano-sized spherical silver powders as auxiliary conductive powders. This achieved the closest possible packing of the silver powders, reducing the bulk resistivity of the silver paste. After low-temperature sintering at 150℃~200℃, the nano-sized spherical silver powder melts. Mixing different forms of silver powder in this ratio allows for the formation of more sintering connection points between the flake-shaped and spherical silver powders, further reducing the bulk resistivity to a final level of 3.3 × 10⁻⁶. 6 However, directly adding nanoscale spherical silver powder can easily lead to agglomeration and is costly.

[0028] In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0029] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0030] In the description of the embodiments of this application, when a component "includes" another component, other components are not excluded unless otherwise stated, and other components may be further included.

[0031] The terminology used in the description of the various embodiments herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used in the description of the various embodiments and the appended claims, the term "component" is also intended to include the plural form unless the context clearly indicates otherwise.

[0032] The embodiments of this application will now be described in detail with reference to the accompanying drawings. However, those skilled in the art will understand that many technical details have been provided in the embodiments of this application to facilitate a better understanding of the application. However, the technical solutions claimed in this application can be implemented even without these technical details and various variations and modifications based on the following embodiments.

[0033] In a first aspect, this application provides a method for manufacturing a solar cell, comprising: Obtain the solar cell body and conductive materials; The conductive material is disposed on the surface of the solar cell body and cured to form a main grid and / or a fine grid. The conductive material contains an MXene@Ag composite material, which comprises MXene material and Ag nanoparticles. The method for preparing the MXene material includes: Ti3AlC2 powder was ground and mixed with metal chloride, and then heated in an oxygen-free atmosphere to obtain the MXene material.

[0034] This application provides a nano-silver modified MXene composite material. Utilizing the active groups on the MXene surface, silver nanoparticles are in-situ reduced onto the MXene. By adjusting the reaction conditions, the size of the prepared silver nanoparticles is maintained below 100 nm, enabling sintering at low temperatures. Introducing this composite material as a conductive reinforcing phase into low-temperature silver paste not only fully leverages the advantages of nano-silver, improving the conductivity of the low-temperature silver paste while also giving it good printability and adhesion properties, but also ensures greater safety by avoiding the use of fluorides in the preparation of the MXene composite material. Furthermore, it prevents the agglomeration of nano-silver, thereby improving the conductivity and stability of the conductive silver paste.

[0035] Optionally, the temperature of the heating reaction is 550℃~800℃.

[0036] Optionally, the mass ratio of the Ti3AlC2 powder to the metal chloride is 3:1 to 8:1.

[0037] Optionally, the metal chloride includes at least one of copper chloride, zinc chloride, and nickel chloride.

[0038] Optionally, the particle size of the MXene material is 0.6μm to 6μm; the D50 of the Ag nanoparticles does not exceed 100nm.

[0039] Optionally, the MXene@Ag composite material has a mass fraction of 1% to 10% in the conductive material.

[0040] Optionally, the conductive material further includes silver powder, an organic carrier, a coupling agent, and a curing agent, wherein the mass fractions of the silver powder, the organic carrier, the coupling agent, and the curing agent in the conductive material are 80%~90%, 10%~18%, 0.1%~0.6%, and 0.1%~0.6%, respectively.

[0041] Optionally, the silver powder includes flake silver powder and spherical silver powder, wherein the mass ratio of the flake silver powder to the spherical silver powder is 2:1 to 3:1.

[0042] Optionally, the particle size of the flake silver powder is 2μm to 6μm, and the particle size of the spherical silver powder is 0.3μm to 0.7μm.

[0043] Optionally, the organic carrier includes a binder, an organic solvent, and a thixotropic agent.

[0044] Optionally, the adhesive includes at least one of bisphenol A type epoxy resin and bisphenol S type epoxy resin; the organic solvent includes at least one of diethylene glycol butyl ether acetate, ethyl carbitol acetate, and propylene glycol methyl ether acetate; and the thixotropic agent includes at least one of hydrogenated castor oil and polyethylene wax.

[0045] Optionally, the coupling agent includes a silane coupling agent, and the curing agent includes at least one of boron trifluoride-monoethylamine complex, 2-methylimidazole, and methylhexahydrophthalic anhydride.

[0046] Optionally, the silane coupling agent includes at least one of epoxy silanes and amino silanes, such as γ-aminopropyltriethoxysilane (KH550).

[0047] Secondly, this application provides a solar cell obtained by the above-described preparation method, such as... Figure 1 As shown, it includes: solar cell body 1, main grid 2 and fine grid 3.

[0048] Thirdly, this application provides a stacked battery, comprising: A crystalline silicon base cell, wherein the crystalline silicon base cell is the solar cell described above, or a solar cell obtained by the manufacturing method of the solar cell described above; A perovskite solar cell, wherein the perovskite solar cell is located on one side of the crystalline silicon substrate solar cell.

[0049] Fourthly, this application provides a photovoltaic module, such as... Figure 2 As shown, it includes a battery string 100, which includes a plurality of the above-described solar cells 101 arranged along a first direction, or solar cells obtained by the above-described solar cell preparation method, or tandem cells as described above, and the plurality of battery strings 100 are also arranged along a second direction. The solder strip 4 extends along a first direction X and is arranged along a second direction Y. The solder strip 4 is used to connect two adjacent solar cells 101 or two stacked cells along the first direction. Back plate 120, the back plate 120 is located on the side of the solder strip 4 away from the back of the battery string 100.

[0050] Preparation Example 1 This preparation example provides a method for preparing MXene@Ag composite materials: S1. Ti3AlC2 powder and CuCl2 were mixed at a mass ratio of 3:1 by grinding. The mixture was then heated at 550℃ for 6 hours in a tube furnace under an Ar atmosphere. After the reaction was completed, the reactants were washed repeatedly by centrifugation with 2 mol / L dilute hydrochloric acid (centrifugation speed of 3500 rpm) to remove impurity ions from the supernatant. The lower precipitate was collected and dried in a vacuum oven at 60℃ for 24 hours to obtain multilayer Ti3C2T with a particle size of 0.6 μm. x MXene powder; S2, Take 1g of Ti3C2T obtained in step S1 x MXene powder was dispersed in deionized water by ultrasonication for 30 minutes to obtain an MXene dispersion. S3. Dissolve 0.05g of AgNO3 in deionized water to obtain an AgNO3 solution; S4. Slowly add the AgNO3 solution obtained in step S3 to the MXene dispersion obtained in step S2, controlling the mass ratio of MXene to AgNO3 to be 2:1. After the AgNO3 solution is added, react for 3 hours under ice bath conditions, then centrifuge and wash the precipitate at 3000 rpm. Finally, obtain the MXene@Ag composite material by vacuum drying at 60℃, wherein the D50 of the Ag nanoparticles does not exceed 100 nm.

[0051] Preparation Example 2 This preparation example provides a method for preparing MXene@Ag composite materials: S1. Ti3AlC2 powder and ZnCl2 were mixed at a mass ratio of 4:1 by grinding. The mixture was then heated at 800℃ for 2 hours in a tube furnace under an Ar atmosphere. After the reaction was completed, the reactants were washed repeatedly by centrifugation with 1 mol / L dilute hydrochloric acid (centrifugation speed of 6000 rpm) to remove impurity ions from the supernatant. The lower precipitate was collected and dried in a vacuum oven at 80℃ for 12 hours to obtain multilayer Ti3C2T with a particle size of 6 μm. x MXene powder; S2, Take 1g of Ti3C2T obtained in step S1 x MXene powder was dispersed in deionized water by ultrasonication for 20 minutes to obtain an MXene dispersion. S3. Dissolve 0.1g of AgNO3 in deionized water to obtain an AgNO3 solution; S4. Slowly add the AgNO3 solution obtained in step S3 to the MXene dispersion obtained in step S2, controlling the mass ratio of MXene to AgNO3 to be 100:1. After the AgNO3 solution is added, react for 3 hours under ice bath conditions, then centrifuge and wash the precipitate at a speed of 5000 rpm. Finally, obtain the MXene@Ag composite material by vacuum drying at 70℃, wherein the D50 of the Ag nanoparticles does not exceed 100 nm.

[0052] Preparation Example 3 This preparation example provides a method for preparing MXene@Ag composite materials: S1. Ti3AlC2 powder and NiCl2 were mixed at a mass ratio of 5:1 by grinding. The mixture was then heated at 700℃ for 4 hours in a tube furnace under an Ar atmosphere. After the reaction was completed, the reactants were washed repeatedly by centrifugation with 1.5 mol / L dilute hydrochloric acid (centrifugation speed of 5000 rpm) to remove impurity ions from the supernatant. The lower precipitate was collected and dried in a vacuum oven at 70℃ for 18 hours to obtain multilayer Ti3C2T with a particle size of 3.3 μm. x MXene powder; S2, Take 1g of Ti3C2T obtained in step S1 x MXene powder was dispersed in deionized water by ultrasonication for 30 minutes to obtain an MXene dispersion. S3. Dissolve 0.03g of AgNO3 in deionized water to obtain an AgNO3 solution; S4. Slowly add the AgNO3 solution obtained in step S3 to the MXene dispersion obtained in step S2, controlling the mass ratio of MXene to AgNO3 to be 50:1. After the AgNO3 solution is added, react for 2 hours under ice bath conditions. Then, centrifuge and wash the precipitate at 3500 rpm. Finally, dry it under vacuum at 80℃ to obtain the MXene@Ag composite material, wherein the D50 of the Ag nanoparticles does not exceed 100 nm.

[0053] Preparation Example 4 This preparation example provides a method for preparing MXene@Ag composite materials: S1. Ti3AlC2 powder and CuCl2 were mixed thoroughly by grinding at a mass ratio of 6:1. Then, the mixture was heated at 600℃ for 5 hours in a tube furnace under an Ar atmosphere. After the reaction was completed, the reactants were washed repeatedly by centrifugation with 1 mol / L dilute hydrochloric acid (centrifugation speed of 4000 rpm) to remove impurity ions from the supernatant. The lower precipitate was collected and finally dried in a vacuum oven at 65℃ for 20 hours to obtain multilayer Ti3C2T with a particle size of 2 μm. xMXene powder; S2, Take 1g of Ti3C2T obtained in step S1 x MXene powder was dispersed in deionized water by ultrasonication for 30 minutes to obtain an MXene dispersion. S3. Dissolve 0.05g of AgNO3 in deionized water to obtain an AgNO3 solution; S4. Slowly add the AgNO3 solution obtained in step S3 to the MXene dispersion obtained in step S2, controlling the mass ratio of MXene to AgNO3 to be 20:1. After the AgNO3 solution is added, react for 3 hours under ice bath conditions, then centrifuge and wash the precipitate at 3000 rpm. Finally, obtain the MXene@Ag composite material by vacuum drying at 60℃, wherein the D50 of the Ag nanoparticles does not exceed 100 nm.

[0054] Preparation Example 5 This preparation example provides a method for preparing MXene@Ag composite materials: S1. Ti3AlC2 powder and CuCl2 were mixed thoroughly by grinding at a mass ratio of 7:1. Then, the mixture was heated at 650℃ for 5.5 h in a tube furnace under an Ar atmosphere. After the reaction was completed, the reactants were washed repeatedly by centrifugation with 2 mol / L dilute hydrochloric acid (centrifugation speed of 4500 rpm) to remove impurity ions from the supernatant. The lower precipitate was collected and finally dried in a vacuum oven at 75℃ for 14 h to obtain multilayer Ti3C2T with a particle size of 5 μm. x MXene powder; S2, Take 1g of Ti3C2T obtained in step S1 x MXene powder was dispersed in deionized water by ultrasonication for 30 minutes to obtain an MXene dispersion. S3. Dissolve 0.05g of AgNO3 in deionized water to obtain an AgNO3 solution; S4. Slowly add the AgNO3 solution obtained in step S3 to the MXene dispersion obtained in step S2, controlling the mass ratio of MXene to AgNO3 to be 10:1. After the AgNO3 solution is added, react for 3 hours under ice bath conditions. Then, centrifuge and wash the precipitate at 3000 rpm. Finally, dry it under vacuum at 60℃ to obtain the MXene@Ag composite material, wherein the D50 of the Ag nanoparticles does not exceed 100 nm.

[0055] Preparation Example 6 This preparation example provides a method for preparing MXene@Ag composite materials: S1. Ti3AlC2 powder and CuCl2 were mixed thoroughly by grinding at a mass ratio of 8:1. The mixture was then heated at 750℃ for 2.5 h in a tube furnace under an Ar atmosphere. After the reaction, the reactants were washed multiple times by centrifugation with 1 mol / L dilute hydrochloric acid (centrifugation speed 5500 rpm) to remove impurity ions from the supernatant. The lower precipitate was collected and dried in a vacuum oven at 65℃ for 22 h to obtain multilayer Ti3C2T with a particle size of 4 μm. x MXene powder; S2, Take 1g of Ti3C2T obtained in step S1 x MXene powder was dispersed in deionized water by ultrasonication for 30 minutes to obtain an MXene dispersion. S3. Dissolve 0.05g of AgNO3 in deionized water to obtain an AgNO3 solution; S4. The AgNO3 solution obtained in step S3 is slowly added dropwise to the MXene dispersion obtained in step S2, and the mass ratio of MXene to AgNO3 is controlled at 60:1. After the AgNO3 solution is added, the mixture is reacted under ice bath conditions for 3 hours. The precipitate is then centrifuged and washed at a speed of 3000 rpm. Finally, the MXene@Ag composite material is obtained by vacuum drying at 60℃, wherein the D50 of the Ag nanoparticles does not exceed 100 nm.

[0056] Preparation of Comparative Example 1 This comparative example provides a method for preparing MXene@Ag composite materials, which differs from preparation example 1 only in that the multilayer Ti3C2T... x The preparation method of MXene powder is as follows: Ti3AlC2 powder was slowly added to hydrofluoric acid, and the mixture was stirred and etched at room temperature for 26 hours. The precipitate was then washed with deionized water by centrifugation at 3500 rpm until the pH of the supernatant was greater than 6. Finally, the mixture was freeze-dried at 60°C for 30 hours to obtain Ti3C2T. x MXene powder.

[0057] Example 1 This embodiment provides a method for manufacturing a solar cell, including the following steps: Obtain the solar cell body and conductive materials; The conductive material is coated onto the surface of the solar cell body and cured at 200°C to form the main grid and fine grid; The methods for preparing conductive materials include: (1) Bisphenol A type epoxy resin, diethylene glycol butyl ether acetate and hydrogenated castor oil are mixed in a mass ratio of 43:56.6:0.4 and stirred in a water bath at 70°C for 50 min at a speed of 500 r / min with a magnetic stirrer to prepare an organic carrier. (2) The MXene@Ag composite material obtained in Preparation Example 1 was thoroughly mixed with micron-sized flake silver powder and submicron-sized spherical silver powder to obtain a mixed conductive phase. Then, the mixed conductive phase was initially mixed with silane coupling agent KH550, boron trifluoride-monoethylamine complex and the organic carrier in step (1). After the initial mixing was completed, the mixed conductive phase and the organic carrier were thoroughly mixed using a three-roll mill to obtain a conductive material with a fineness of less than 6 μm. Among them, based on the total mass of the conductive material, the mass fractions of MXene@Ag composite material, flake silver powder, spherical silver powder, silane coupling agent KH550, boron trifluoride-monoethylamine complex and organic carrier were 1%, 56%, 25%, 0.4%, 0.4% and 17.2%, respectively. The particle size of the flake silver powder was 2 μm and the particle size of the spherical silver powder was 0.7 μm.

[0058] Example 2 This embodiment provides a method for manufacturing a solar cell, including the following steps: Obtain the solar cell body and conductive materials; The conductive material is coated onto the surface of the solar cell body and cured at 200°C to form the main grid and fine grid; The methods for preparing conductive materials include: (1) Bisphenol A type epoxy resin, diethylene glycol butyl ether acetate and hydrogenated castor oil were mixed in a mass ratio of 44:55.5:0.5 and stirred in a water bath at 600 r / min for 55 min at 65°C using a magnetic stirrer to prepare an organic carrier. (2) The MXene@Ag composite material obtained in Preparation Example 1 was thoroughly mixed with micron-sized flake silver powder and submicron-sized spherical silver powder to obtain a mixed conductive phase. Then, the mixed conductive phase was initially mixed with silane coupling agent KH550, boron trifluoride-monoethylamine complex and the organic carrier in step (1). After the initial mixing was completed, the mixed conductive phase and the organic carrier were thoroughly mixed using a three-roll mill to obtain a conductive material with a fineness of less than 6 μm. Based on the total mass of the conductive material, the mass fractions of MXene@Ag composite material, flake silver powder, spherical silver powder, silane coupling agent KH550, boron trifluoride-monoethylamine complex and organic carrier were 3%, 56%, 25%, 0.4%, 0.4% and 15.2%, respectively. The particle size of the flake silver powder was 6 μm and the particle size of the spherical silver powder was 0.3 μm.

[0059] Example 3 This embodiment provides a method for manufacturing a solar cell, including the following steps: Obtain the solar cell body and conductive materials; The conductive material is coated onto the surface of the solar cell body and cured at 200°C to form the main grid and fine grid; The methods for preparing conductive materials include: (1) Bisphenol A type epoxy resin, ethyl carbitol acetate and hydrogenated castor oil were mixed in a mass ratio of 42:57.6:0.4 and stirred in a water bath at 600 r / min for 55 min at 65°C using a magnetic stirrer to prepare an organic carrier. (2) The MXene@Ag composite material obtained in Preparation Example 1 was thoroughly mixed with micron-sized flake silver powder and submicron-sized spherical silver powder to obtain a mixed conductive phase. Then, the mixed conductive phase was initially mixed with silane coupling agent KH550, boron trifluoride-monoethylamine complex and the organic carrier in step (1). After the initial mixing was completed, the mixed conductive phase and the organic carrier were thoroughly mixed using a three-roll mill to obtain a conductive material with a fineness of less than 6 μm. Among them, based on the total mass of the conductive material, the mass fractions of MXene@Ag composite material, flake silver powder, spherical silver powder, silane coupling agent KH550, boron trifluoride-monoethylamine complex and organic carrier were 5%, 56%, 25%, 0.4%, 0.4% and 13.2%, respectively. The particle size of the flake silver powder was 4 μm and the particle size of the spherical silver powder was 0.5 μm.

[0060] Example 4 This embodiment provides a method for manufacturing a solar cell, including the following steps: Obtain the solar cell body and conductive materials; The conductive material is coated onto the surface of the solar cell body and cured at 200°C to form the main grid and fine grid; The methods for preparing conductive materials include: (1) Bisphenol A type epoxy resin, diethylene glycol butyl ether acetate and hydrogenated castor oil are mixed in a mass ratio of 43:56.6:0.4 and stirred in a water bath at 70°C for 50 min at a speed of 500 r / min with a magnetic stirrer to prepare an organic carrier. (2) The MXene@Ag composite material obtained in Preparation Example 1 was thoroughly mixed with micron-sized flake silver powder and submicron-sized spherical silver powder to obtain a mixed conductive phase. Then, the mixed conductive phase was initially mixed with silane coupling agent KH550, boron trifluoride-monoethylamine complex and the organic carrier in step (1). After the initial mixing was completed, the mixed conductive phase and the organic carrier were thoroughly mixed using a three-roll mill to obtain a conductive material with a fineness of less than 6 μm. Among them, based on the total mass of the conductive material, the mass fractions of MXene@Ag composite material, flake silver powder, spherical silver powder, silane coupling agent KH550, boron trifluoride-monoethylamine complex and organic carrier were 5%, 60%, 20%, 0.4%, 0.4% and 14.2%, respectively. The particle size of the flake silver powder was 2 μm and the particle size of the spherical silver powder was 0.3 μm.

[0061] Example 5 This embodiment provides a method for manufacturing a solar cell, including the following steps: Obtain the solar cell body and conductive materials; The conductive material is coated onto the surface of the solar cell body and cured at 200°C to form the main grid and fine grid; The methods for preparing conductive materials include: (1) Bisphenol A type epoxy resin, diethylene glycol butyl ether acetate and hydrogenated castor oil are mixed in a mass ratio of 43:56.6:0.4 and stirred in a water bath at 70°C for 50 min at a speed of 500 r / min with a magnetic stirrer to prepare an organic carrier. (2) The MXene@Ag composite material obtained in Preparation Example 1 was thoroughly mixed with micron-sized flake silver powder and submicron-sized spherical silver powder to obtain a mixed conductive phase. Then, the mixed conductive phase was initially mixed with silane coupling agent KH550, boron trifluoride-monoethylamine complex and the organic carrier in step (1). After the initial mixing was completed, the mixed conductive phase and the organic carrier were thoroughly mixed using a three-roll mill to obtain a conductive material with a fineness of less than 6 μm. Based on the total mass of the conductive material, the mass fractions of MXene@Ag composite material, flake silver powder, spherical silver powder, silane coupling agent KH550, boron trifluoride-monoethylamine complex and organic carrier were 10%, 56%, 25%, 0.4%, 0.4% and 8.2%, respectively. The particle size of the flake silver powder was 6 μm and the particle size of the spherical silver powder was 0.7 μm.

[0062] Comparative Example 1 The difference between this comparative example and Example 3 is that no multilayer MXene@Ag composite material was added, the mass ratio of flake silver powder, spherical silver powder, silane coupling agent KH550 and boron trifluoride-monoethylamine complex remained unchanged, and the mass fraction of the organic carrier was 18.2%. Comparative Example 2 The difference between this comparative example and Example 3 is that MXene@Ag composite material is not added, the mass ratio of spherical silver powder, silane coupling agent KH550, boron trifluoride-monoethylamine complex and organic carrier remains unchanged, and the mass fraction of flake silver powder is 61%.

[0063] Comparative Example 3 The difference between this comparative example and Example 3 is that MXene@Ag composite material is not added, the mass ratio of flake silver powder, silane coupling agent KH550, boron trifluoride-monoethylamine complex and organic carrier remains unchanged, and the mass fraction of spherical silver powder is 30%.

[0064] Comparative Example 4 The difference between this comparative example and Example 3 is that the MXene@Ag composite material was replaced with the MXene@Ag composite material used in Comparative Example 1.

[0065] Comparative Example 5 The difference between this comparative example and Example 3 is that the curing temperature is 150°C.

[0066] The conductive materials prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to the following tests: 1. Volume resistivity test: The prepared conductive material is printed on a PET film by screen printing. After low-temperature curing at 200℃, the sheet resistance of the silver electrode is tested by a four-probe tester, and the thickness of the silver electrode is tested by a film thickness gauge. Finally, the volume resistivity is calculated.

[0067] 2. Adhesion rating test: The prepared conductive material is printed on PET film by screen printing, and the adhesion rating test is carried out using the 3M cross-cut adhesion test.

[0068] 3. Rheological testing: The rheological properties of the low-temperature silver paste were tested using an RST rheometer.

[0069] Table 1

[0070] The volume resistivity of the silver electrode prepared using the conductive material obtained in Example 3 is 3.87 × 10⁻⁶. -6 The volume resistivity of the silver electrode prepared from the conductive material obtained in Comparative Example 1 is 1.24 × 10 Ω / cm. -5The volume resistivity of the conductive slurry obtained in Comparative Example 1 is higher than that in Example 3 because the absence of MXene@Ag composite material increased the content of the organic carrier, reduced the conductive pathways formed between the conductive fillers, and the lack of sintering bridging effect of silver nanoparticles led to an increase in interfacial resistance. -6 The volume resistivity of the conductive slurry obtained in Comparative Example 2 is higher than that in Example 3. This is because MXene has a higher packing density, resulting in a higher volume fraction and greater dispersion in the slurry system, thus forming more conductive pathways. Furthermore, the silver nanoparticles generated during the reduction of MXene surface undergo sintering to form bridging effects, reducing interfacial resistance. These factors contribute to the higher volume resistivity of the conductive slurry obtained in Comparative Example 2 compared to Example 3. The volume resistivity of the silver electrode prepared from the conductive material obtained in Comparative Example 3 is 7.16 × 10⁻⁶ Ω / cm. -6 The volume resistivity of the silver electrode prepared from the conductive material obtained in Comparative Example 4 is 4.21 × 10⁻⁶ Ω / cm. This is because MXene has a high packing density, resulting in a higher volume fraction and greater dispersion in the slurry system, thus forming more conductive pathways. Furthermore, the sintering of silver nanoparticles generated on the MXene surface creates bridging, reducing interfacial resistance. Additionally, the point contact between the spherical silver powder and the conductive filler leads to an increase in interfacial resistance. -6 The conductivity is Ω / cm because MXene prepared by fluorine-containing methods is easily oxidized due to the presence of -F end groups, which leads to a decrease in conductivity. In addition, since -F is a hydrophobic end group, it is prone to aggregation and has poor compatibility with polymers and interfaces.

[0071] Comparative Example 5, used as a comparison of curing conditions, only changed the curing temperature. This is because this comparative example is intended to illustrate that the silver nanoparticles generated by reduction on MXene need to reach around 200°C to be effectively sintered, thereby forming contact with the connected conductive filler, reducing interfacial resistance, and improving conductivity. However, the curing temperature in Comparative Example 5 was only 150°C, during which the silver nanoparticles could not sinter and could only form a conductive path through simple contact, resulting in a large interfacial resistance and thus affecting conductivity (the difference between overlapping and welding).

[0072] Those skilled in the art will understand that the above embodiments are specific examples of implementing this application, and in practical applications, various changes in form and detail can be made without departing from the spirit and scope of this application. Any person skilled in the art can make various alterations and modifications without departing from the spirit and scope of this application; therefore, the scope of protection of this application should be determined by the scope defined in the claims.

Claims

1. A method for manufacturing a solar cell, characterized in that, include: Obtain the solar cell body and conductive materials; The conductive material is disposed on the surface of the solar cell body and cured to form a main grid and / or a fine grid. The conductive material contains an MXene@Ag composite material, which comprises MXene material and Ag nanoparticles. The method for preparing the MXene material includes: Ti3AlC2 powder and metal chloride were ground and mixed, and then heated in an oxygen-free atmosphere to obtain the MXene material.

2. The method for manufacturing a solar cell according to claim 1, characterized in that, The temperature of the heating reaction is 550℃~800℃.

3. The method for manufacturing a solar cell according to claim 1, characterized in that, The mass ratio of Ti3AlC2 powder to metal chloride is 3:1 to 8:

1.

4. The method for manufacturing a solar cell according to claim 1 or 3, characterized in that, The metal chloride includes at least one of copper chloride, zinc chloride, and nickel chloride.

5. The method for manufacturing a solar cell according to claim 1, characterized in that, The particle size of the MXene material is 0.6μm to 6μm; the D50 of the Ag nanoparticles does not exceed 100nm.

6. The method for manufacturing a solar cell according to claim 1, characterized in that, The MXene@Ag composite material has a mass fraction of 1% to 10% in the conductive material.

7. The method for manufacturing a solar cell according to claim 1 or 6, characterized in that, The conductive material further includes silver powder, an organic carrier, a coupling agent, and a curing agent, wherein the mass fractions of the silver powder, the organic carrier, the coupling agent, and the curing agent in the conductive material are 80%~90%, 10%~18%, 0.1%~0.6%, and 0.1%~0.6%, respectively.

8. The method for manufacturing a solar cell according to claim 7, characterized in that, The silver powder includes flake silver powder and spherical silver powder, and the mass ratio of the flake silver powder to the spherical silver powder is 2:1 to 3:

1.

9. The method for manufacturing a solar cell according to claim 8, characterized in that, The particle size of the flake-shaped silver powder is 2μm~6μm, and the particle size of the spherical silver powder is 0.3μm~0.7μm.

10. The method for manufacturing a solar cell according to claim 7, characterized in that, The organic carrier includes a binder, an organic solvent, and a thixotropic agent.

11. The method for manufacturing a solar cell according to claim 10, characterized in that, The adhesive includes at least one of bisphenol A type epoxy resin and bisphenol S type epoxy resin; the organic solvent includes at least one of diethylene glycol butyl ether acetate, ethyl carbitol acetate, and propylene glycol methyl ether acetate; the thixotropic agent includes at least one of hydrogenated castor oil and polyethylene wax.

12. The method for manufacturing a solar cell according to claim 7, characterized in that, The coupling agent includes a silane coupling agent, and the curing agent includes at least one of boron trifluoride-monoethylamine complex, 2-methylimidazole, and methylhexahydrophthalic anhydride.

13. A solar cell obtained by a method of manufacturing a solar cell according to any one of claims 1 to 12.

14. A stacked battery, characterized in that, include: A crystalline silicon bottom cell, wherein the crystalline silicon bottom cell is a solar cell obtained by the manufacturing method of a solar cell according to any one of claims 1 to 12, or a solar cell according to claim 13; A perovskite solar cell, wherein the perovskite solar cell is located on one side of the crystalline silicon substrate solar cell.

15. A photovoltaic module, characterized in that, The battery string includes a plurality of solar cells obtained by the manufacturing method of any one of claims 1 to 12, arranged along a first direction, or a solar cell as claimed in claim 13, or a tandem cell as claimed in claim 14, and the plurality of battery strings are further arranged along a second direction; A solder strip extending along a first direction and arranged along a second direction, the solder strip being used to connect two adjacent solar cells or two stacked cells along the first direction; A backplate, located on the side of the solder strip away from the back of the battery string.